2017
DOI: 10.7150/ijbs.17318
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to vitiligo treatment via modulation of mTOR and NF-κB pathways in human skin melanocytes

Abstract: Vitiligo is a skin depigmentation disorder with an increasing prevalence. Among recognized mechanisms is the oxidative stress that affects melanocytes which are responsible for skin pigmentation. Studies have shown that high concentration of hydrogen peroxide, or H2O2, induces apoptotic activities. Few studies have been done with lower doses of H2O2. Using human skin melanocytes, we investigated the effect of moderate concentration of H2O2 on melanocyte dendrites. Confocal data show that H2O2 at 250 µM induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Furthermore, another study suggested that α-melanocyte-stimulating hormone stimulated melanogenesis through activating the mitogen-activated protein kinase kinase/ERK or PI3K/AKT pathways (20). Regulation of the PI3K/AKT/mTOR signaling pathway has been reported to be a novel approach for the clinical treatment of vitiligo (21). Moreover, the association between RIPK1 and the PI3K/AKT/mTOR pathway in melanocytes under ER stress remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another study suggested that α-melanocyte-stimulating hormone stimulated melanogenesis through activating the mitogen-activated protein kinase kinase/ERK or PI3K/AKT pathways (20). Regulation of the PI3K/AKT/mTOR signaling pathway has been reported to be a novel approach for the clinical treatment of vitiligo (21). Moreover, the association between RIPK1 and the PI3K/AKT/mTOR pathway in melanocytes under ER stress remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…a previous study indicated that nrf2 negatively regulates melanogenesis by modulating the Pi3K/akt signaling pathway (42). The α-MSH-induced activation of the mTorc1 pathway, inhibited by rapamycin, helps to maintain dendrites of melanocytes under oxidative stress (26). Sustained Pi3K activity can protect melanocytes from apoptosis, thereby indicating that the Pi3K/aKT pathway plays a pivotal role in melanocyte survival (43).…”
Section: Discussionmentioning
confidence: 97%
“…in addition, indirect data indicated that α-MSH stimulated melanogenesis through the activation of the MeK/erK or Pi3K/aKT pathways (25). Modulation of the Pi3K/aKT and mTor pathway may be a novel approach to the clinical management of vitiligo (26). a previous study indicated that nrf2 negatively regulates melanogenesis by modulating the Pi3K/akt signaling pathway (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism involved in this type of druginduced vitiligo isn't completely clear, we can suppose that one of the pathogenetic mechanisms is that everolimus can inhibit melanogenesis, by inhibiting the protective mTORC1 pathway against oxidative stress. 16 Our case can suggest a new possible type of drug melanocyte-specific toxicity.…”
Section: Discussionmentioning
confidence: 99%